Design of Mobile Learning for Mathematics Subjects on Building Volume Materials for Class V Students at SD Negeri 1 Jatikuwung, Karanganyar - Niko Wijanarko; Tinuk Agustin; Muhammad Setiyawan (PT FORMOSA CENDEKIA GLOBAL, 2023)
Education plays a significant role in enriching people's lives and building a better future. Mathematics has universal characteristics and has an important role in various fields of science. Grade V students at SD Negeri 01 Jatikuwung, Karanganyar. There is still a lack of interest in learning mathematics in the material of geometric volumes. Mobile Learning can help increase students' interest in learning mathematics. In making this mobile learning using the MIT App Inventor software. The design of mobile learning uses the ADDIE research method (Analysis, Design, Development, Implementation and Evaluation). This mobile learning design was also tested using Black Box testing, from Black box testing how many functionalities of the 9 tests the results were